2019
DOI: 10.1007/s00253-019-09861-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbially induced calcium carbonate precipitation: a widespread phenomenon in the biological world

Abstract: Bio-deposition of minerals is a widespread phenomenon in the biological world and is mediated by bacteria, fungi, protists, and plants. Calcium carbonate is one of those minerals that naturally precipitates as a by-product of microbial metabolic activities. Over recent years, microbially induced calcium carbonate precipitation (MICP) has been proposed as a potent solution to address many environmental and engineering issues. However, for being a viable alternative to conventional techniques as well as being fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(91 citation statements)
references
References 149 publications
1
86
0
4
Order By: Relevance
“…Microbe‐induced calcite precipitation by urease‐producing bacteria is a potential solution to address these issues ( Figure A). [ 272 ] Urease catalyzes the hydrolysis of urea into ammonium and carbamate. Carbamate is spontaneously hydrolyzed to carbonic acid and ultimately to bicarbonate by carbonic anhydrase.…”
Section: Applicationsmentioning
confidence: 99%
“…Microbe‐induced calcite precipitation by urease‐producing bacteria is a potential solution to address these issues ( Figure A). [ 272 ] Urease catalyzes the hydrolysis of urea into ammonium and carbamate. Carbamate is spontaneously hydrolyzed to carbonic acid and ultimately to bicarbonate by carbonic anhydrase.…”
Section: Applicationsmentioning
confidence: 99%
“…The different reactions and byproducts generated in the formation of calcite using the various MICP processes stated above are as follows: [72].…”
Section: Mechanisms Of Microbially Induced Calcite Precipitationmentioning
confidence: 99%
“…Among these applications are amending or improving construction materials and remediation of cracks/self-healing in concrete [3, 72, 79-86, 102, 118-122], as well as cementation of porous media and improvements in strength and stiffness [6,7,26,35,103,117,121,123]. It is also used in environmental remediation of heavy metals and radionuclides, including the potential to reduce subsurface leakage in the background of geologically isolated carbon dioxide [72,104,105,[124][125][126][127][128][129][130][131][132][133][134][135]. Recent studies [136] have reported MICP as a conservative method for restoring the lost strength in decayed limestone through biomineralization processes, for trial tests in both laboratory and field conditions.…”
Section: Micp Applicationsmentioning
confidence: 99%
“…(2015) . There are bacteria that can precipitate calcite to heal cracks in concretes, which enhances its durability . Hammes et al.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18][19] There are bacteria that can precipitate calcite to heal cracks in concretes, which enhances its durability. [20][21][22][23] Hammes et al (2003) [22] and Bachmeier et al (2002) [24] also used the microbial urease activity with different factors. Technique MICP is considered natural and pollution free.…”
Section: Self-healing Of Concrete Samplementioning
confidence: 99%